Training on Utilization of Wordwall Media os Online-Based Learning Assessment For Elementary School Teachers 08 Supayang - Rahmi, Lailatur; Angraina, Dilla (Sumatra Journal of Disaster, Geography and Geography Education, 2021)
This activity aims to guide and form teachers at the state elementary school 08 Supayang, Payung Sekaki, Solok Regency to become creative teachers to provide learning for their students. This is realized by providing training on the use of the wordwall application as a remote assessment medium. This application makes it easier for teachers and students to access learning assessments from anywhere and anytime. The wordwall application offers templates that can be used to make assessments and can be used for free. The approach methods offered to support the realization of this community service program are; (1) program socialization in order to provide teachers with a view to include technology in the learning process and provide teachers with information about interactive learning media that can be used to support the learning process, so that the lessons presented can attract the interest and attention of students, (2) The design of the preparation of activities that will be carried out in the field is in the form of looking for experts or experts who will provide training materials and guidance on the creation and management of online learning evaluation applications in the form of the Wordwall application, and (3) conducting workshops and training on account creation and how to use the Wordwall application as a learning assessment. This community service activity changes the teachers' view that technology plays a major role in supporting the learning process to achieve learning goals. The technology in question is utilizing media that are already available online on the internet. One of them is the wordwall application which is used as a remote evaluation medium. The wordwall application offers various and interesting templates. Teachers are guided to create accounts and evaluation materials in the wordwall application and how to use them. One of the available templates is Quiz, wordsearch, true false and many others. This application has an attractive appearance and easy and inexpensive access. This application can be accessed using the internet network.